Extended fisheries recovery timelines in a changing environment - Gregory L. Britten (Nature Portfolio, 2017)
Many estimates of fisheries recovery time currently assume that the environment and associated fish population dynamics are fixed. Brittenet al. use Bayesian models incorporating variation in productivity and carrying capacity to provide revised estimates of recovery timelines for depleted fish stocks worldwide.